2010
DOI: 10.1510/icvts.2010.243253
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery branch – jejunal artery aneurysm☆

Abstract: Visceral artery aneurysm (VAA) is a relatively uncommon disorder and it shows some vague symptoms. Therefore, the clinical diagnosis is difficult and these aneurysms are discovered and diagnosed only after rupture in many cases. This case report describes the history of a woman who had a superior mesenteric artery (SMA) branch aneurysm. A 62-year-old woman presented with fatigue and moderate to severe epigastric and mid-back pain. A computed tomography of the abdomen and pelvis demonstrated a partially thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…Therefore, complications of this small aneurysm affect the treatment strategy. Kurdal et al also reported rupture of the aneurysm of the jejunal branch of the superior mesenteric artery, similar to our case [ 4 ]. The second branch of SMA that is likely to be the jejunal branch was involved in our case.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, complications of this small aneurysm affect the treatment strategy. Kurdal et al also reported rupture of the aneurysm of the jejunal branch of the superior mesenteric artery, similar to our case [ 4 ]. The second branch of SMA that is likely to be the jejunal branch was involved in our case.…”
Section: Discussionsupporting
confidence: 89%
“…Various treatment procedures have been reported for the treatment of SMAA with intestinal ischemia or rupture. Surgery is usually performed, according to the recent studies [ 4 ]. Multiple surgical techniques have been described including ligation and bypass with autologous graft, thrombectomy and fixation of an intimal flap.…”
Section: Discussionmentioning
confidence: 99%
“…[34] The most common causes of aneurysm are atherosclerosis, angiodysplasias, arteritis and infection. [35] However, in our case, arteritis seems to be responsible because of raised leukocytes and C-reactive protein as well as mesenteric enhancement on the CT scan. These aneurysms are usually asymptomatic but rupture, thrombosis and distal embolization have been reported frequently.…”
Section: Discussionmentioning
confidence: 53%
“…These aneurysms are usually asymptomatic but rupture, thrombosis and distal embolization have been reported frequently. [35] These complications can be life threatening; as the incidence of spontaneous rupture reaches up to 50%. [6] Due to the presence of good collateral circulation these aneurysms are often amenable to ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not uncommon that the aneurysm is only discovered after rupture, with hypovolaemic shock, leading to an increased mortality 9. The initial diagnosis in an emergent situation depends on the suspicion.…”
Section: Discussionmentioning
confidence: 99%